Comparative antiplaque and antigingivitis efficacy of three antiseptic mouthrinses: a two week randomized clinical trial - Amini,Pejmon (2009)
The objective of this randomized, examiner blind, parallel group, controlled clinical trial was to compare the antiplaque and antigingivitis efficacy of an essential oil-containing mouthrinse (EO) to two mouthrinses containing 0.05% Cetylpyridinium Chloride (CPC), one with alcohol and one alcohol-free, using a two-week experimental gingivitis validated-model with a 5% hydroalcohol rinse serving as the negative control. One hundred and fifty-nine subjects, 56 males and 103 females; ranging in age from 18 to 58 years in good general health were assigned to one of the four treatment groups: EO (n = 40), 0.05% CPC with alcohol (CPCa, n = 39), 0.05% CPC alcohol-free (CPCna, n = 40), and 5% hydroalcohol negative control (n = 40). The Mean Turesky Modification of the Quigley-Hein Plaque Index (PI) and the Mean Modified Gingival Index (MGI) were the primary efficacy endpoints and were evaluated at baseline and at two weeks. Following baseline examinations, subjects received a complete dental prophylaxis and began supervised rinsing with their assigned mouthrinse twice daily for two weeks, as their sole oral hygiene measure; 151 subjects completed the trial. Two weeks after baseline the EO adjusted mean PI and MGI scores were significantly lower than those of both CPC rinses and negative control (p < 0.001). In conclusion, the EO mouthrinse demonstrated significantly greater antiplaque and antigingivitis efficacy than both CPC-containing mouthrinses and the negative control.